Selenium status affects selenoprotein expression, reproduction, and F1 generation locomotor activity in zebrafish (Danio rerio). Issue 11 (14th June 2014) - Penglase, Sam; Hamre, Kristin; Rasinger, Josef D.; Ellingsen, Staale
<x content-type="archive" xml:space="preserve">Abstract</x> Se is an essential trace element, and is incorporated into selenoproteins which play important roles in human health. Mammalian selenoprotein-coding genes are often present as paralogues in teleost fish, and it is unclear whether the expression patterns or functions of these fish paralogues reflect their mammalian orthologues. Using the model species zebrafish (Danio rerio; ZF), we aimed to assess how dietary Se affects key parameters in Se metabolism and utilisation including glutathione peroxidase (GPX) activity, the mRNA expression of key Se-dependent proteins (gpx1a, gpx1b, sepp1a and sepp1b), oxidative status, reproductive success and F1 generation locomotor activity. From 27 d until 254 d post-fertilisation, ZF were fed diets with graded levels of Se ranging from deficient ( < 0·10 mg/kg) to toxic (30 mg/kg). The mRNA expression of gpx1a and gpx1b and GPX activity responded in a similar manner to changes in Se status. GPX activity and mRNA levels were lowest when dietary Se levels (0·3 mg/kg) resulted in the maximum growth of ZF, and a proposed bimodal mechanism in response to Se status below and above this dietary Se level was identified. The expression of the sepp1 paralogues differed, with only sepp1a responding to Se status. High dietary Se supplementation (30 mg/kg) decreased reproductive success, while the offspring of ZF fed above 0·3 mg Se/kg diet had lower locomotor activity than the other groups. Overall, the novel finding of low selenoprotein expression and activity coinciding with maximum body growth suggests that even small Se-induced variations in redox status may influence cellular growth rates.